Usulan Perancangan Ulang Tata Letak Fasilitas Untuk Meningkatkan Efisiensi Pada Area Produksi (Studi Kasus: PT. XYZ) - Bima Maulana; Siti Mundari (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
PT. XYZ is a company operating in the printing sector. The main function of the company is to print various official documents such as diplomas, permits and others. The company is also involved in the publication of books and other public prints. The problem here is the layout of the production facility, which does not take into account the proximity between the departments of the workplace, resulting in distant material movements as well as increased material handling costs. The aim of this research is to redesign the new layout of the production facility to improve material handling efficiency and reduce transport costs. The method used in this design is Systematic Layout Planning, which analyses the degree of proximity between departments using Activity Relationship Chart and Activity Relationship Diagram techniques to describe the departmental layout relative to each other. The results obtained in this research were to reduce the material transportation distance by 1,391,409 cm/month or equivalent of 32.88%, and to reduce the transportation time by 10,013.82 seconds/month or equivalent of 34.85%, as well as to reduce the material handling cost by Rp. 142,247/month or equivalent of 32.57%.